2000
DOI: 10.1038/sj.mp.4000803
|View full text |Cite
|
Sign up to set email alerts
|

Association study of the low-activity allele of catechol-O-methyltransferase and alcoholism using a family-based approach

Abstract: Catechol-O-methyltransferase (COMT) is a major component of the metabolic pathways of neurotransmitters such as dopamine, adrenaline, and noradrenaline. The activity of COMT is known to vary within the population; it exists in common high-and low-activity forms that are determined by a Val → Met polymorphism at amino acid position 108/158 (in soluble or membranebound COMT). Recently, the low-activity allele was reported to contribute to the development of late-onset alcoholism in men. 1 The present study exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 17 publications
3
46
1
1
Order By: Relevance
“…Due to the ascertainment and recruitment strategy, it was possible to perform analyses considering only those with early onset alcohol dependence. Previous analyses (Wang et al, 2001) reported that although there was no overall association between the Val158Met polymorphism and alcoholism in a study of 70 trios, nor in other subsets of the data based on gender or age, the Met158 allele was preferentially associated with early onset alcoholism in a subset of 28 trios having a male proband. In the present, larger family study, we found no evidence of association of the Val158Met polymorphism with either alcoholism or early onset alcoholism (Table 1), although the latter discrepancy may be due to our inclusion of females.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the ascertainment and recruitment strategy, it was possible to perform analyses considering only those with early onset alcohol dependence. Previous analyses (Wang et al, 2001) reported that although there was no overall association between the Val158Met polymorphism and alcoholism in a study of 70 trios, nor in other subsets of the data based on gender or age, the Met158 allele was preferentially associated with early onset alcoholism in a subset of 28 trios having a male proband. In the present, larger family study, we found no evidence of association of the Val158Met polymorphism with either alcoholism or early onset alcoholism (Table 1), although the latter discrepancy may be due to our inclusion of females.…”
Section: Discussionmentioning
confidence: 99%
“…The Met158 allele has been associated with late onset alcoholism in men Tiihonen et al, 1999). This same allele has been associated with early onset alcoholism in one study (Wang et al, 2001) but not in others Ishiguro et al, 1999). The Met158 allele has also been associated with elevated weekly alcohol consumption in male social drinkers .…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…A genetic polymorphism results in three-to four-fold differences in COMT activity (Grossman et al, 1992). Studies that tried to associate the low activity (L) allele of COMT with alcoholism revealed contradictory results Tiihonen et al, 1999;Ishiguro et al, 1999;Wang et al, 2001). Men with the LL genotype have shown a significantly higher weekly alcohol consumption than individuals with other genotypes .…”
Section: Introductionmentioning
confidence: 99%